TEACHING READING COMPREHENSION BY USING COOPERATIVE LEARNING METHOD TO THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM FKIP UNIVERSITAS MUHAMMADIYAH PALEMBANG - Sri Yuliani (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2016)
TEACHING READING COMPREHENSION BY USING COOPERATIVE LEARNING METHOD TO THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM FKIP UNIVERSITAS MUHAMMADIYAH PALEMBANG Sri Yuliani English Education Study Program, Muhammadiyah University, Palembang, Indonesia sriyuliani1771@yahoo.co.id Â Â Abstract: The aim of this research was to find out whether or not it is effective to teach reading comprehension by using Cooperative Learning method to the fourth semester students of English Education Study Program FKIP, Muhammadiyah University, Palembang. The 80 sample students who were the fourth semester students wereselected by using convenience non-random sampling. To collect the data, a test consisting of 25 items in form of multiple choices was given to the students. The data was statistically analysed by using t- test. The results of this study showed that the mean scores for pretest of the experimental group was 64.90 and the post test was 82.60. Meanwhile, the mean scores for pretest of the control group was 59.90 and the post test was 66.10. The result of the independent sample t-test showed that the mean difference between the post test score of experimental and control groups was 22.70, with significance value (2-tailed) 0.000, which was lower than the significant level 0.05. This shows that there was a significant difference in the reading comprehension achievement between the students who were taught by using Cooperative Learning method and those who were not taught by using Cooperative Learning method. It is intepreted that teaching reading comprehension by using Cooperative Learning method was effective. Keywords: teaching, reading comprehension, Cooperative-Learning method